Nodule INception-independent epidermal events lead to bacterial entry during nodule development in peanut (Arachis hypogaea) - Bhattacharjee, Oindrila (The New phytologist, 2022)
© 2022 The Authors. New Phytologist © 2022 New Phytologist Foundation.